Characteristics of rapidly recombining plasmas suitable for high-gain X-ray laser action - Zhang, J; Norreys, P; Tallents, G; Danson, C; Dwiveedi, L; Holden, M; Holden, P; Key, M; Lewis, C; Macphee, A; Neely, D; Pert, G; et al. (1996)
Recombining plasmas produced by picosecond laser pulses are characterized by measuring ratio of intensities of resonance lines of H- and He-like ions in the plasmas. It is found that the rapidly recombining plasmas produced by picosecond laser pulses are suitable for high-gain operation.